Incidence and risk factors contributing to ileus after posterior approach for lumbar surgery: a retrospective study - Bao, Rui; Liang, GuoLei; Liu, YiNan; Wang, Dan; Ma, Rui; Cui, YiZhi; Tian, YangYang; Wang, Le; Guan, Fulin (Frontiers in Surgery, 2025)
ObjectiveThis retrospective study aimed to identify the incidence and possible predictive factors associated with ileus after posterior approach for lumbar surgery.Patients and methodsA total of 267 patients who underwent a posterior approach for lumbar surgery between 2012 and 2020 were analyzed in this study. The differences between the two groups and the risk factors of ileus were explored.ResultsPatients’ characteristics showed no significant differences between the two groups. This revealed that gender, age, smoking, hypertension, and diabetes were not associated with postoperative ileus (POI). Patients with POI would increase length of hospital stay significantly (p = 0.015). Operative segment [odds ratio (OR): 1.40, 3.33; p = 0.04 and 0.02], postoperative blood potassium (OR: 0.92, 0.31; p = 0.04), and previous abdominal surgery (OR: 3.02, p = 0.01) were significant independent risk factors for POI. Operation time, blood loss, and anesthesia type were not considered risk factors for POI.ConclusionPostoperative ileus can increase the length of hospital stay significantly. Operative segment, postoperative blood potassium, and previous abdominal surgery were significantly associated with POI, which should be highlighted in the preoperative evaluation.